Estudo da influência do tratamento térmico de envelhecimento a 475°c nas propriedades mecânicas do aço inoxidável Superduplex UNS S32750 - Valentim, Bruno Lopes (2013)
The duplex stainless steels are composed of a proportion of 50% phases of ferrite and 50% austenite. This ratio gives them good mechanical properties and corrosion resistance, which explains the heavy use that these materials have in industries such as in the oil and gas, pulp and paper, nuclear, among others. Due to the temperature of some processes in which these materials are used, there is risk of embrittlement by the formation of alpha prime phase (α '). This phenomenon occurs between the temperatures of 300 to 550 ° C and increased to 475 ° C, this phenomenon is called embrittlement at 475 ° C. In this study has characterized the mechanical behavior of steel UNS S32750 (SAF 2507) at the conditions: as received, aged for 4, 8 and 12 hours. It was observed the increase of the strength and hardness of the material in detriment of their ductility.